The G‐protein‐coupled chemoattractant receptor Fpr2 exacerbates neuroglial dysfunction and angiogenesis in diabetic retinopathy. Issue 10 (15th September 2020) - Yu, Ying; Xue, Shengding; Chen, Keqiang; Le, Yingying; Zhu, Rongrong; Wang, Shiyi; Liu, Shuang; Cheng, Xinliang; Guan, Huaijin; Wang, Ji Ming; Chen, Hui
Abstract: Diabetic retinopathy (DR) as a retinal neovascularization‐related disease is one of the leading causes of irreversible blindness in patients. The goal of this study is to determine the role of a G‐protein‐coupled chemoattractant receptor (GPCR) FPR2 (mouse Fpr2) in the progression of DR, in order to identify novel therapeutic targets. We report that Fpr2 was markedly upregulated in mouse diabetic retinas, especially in retinal vascular endothelial cells, in associated with increased number of activated microglia and Müller glial cells. In contrast, in the retina of diabetic Fpr2 −/− mice, the activation of vascular endothelial cells and glia was attenuated with reduced production of proinflammatory cytokines. Fpr2 deficiency also prevented the formation of acellular capillary during diabetic progression. Furthermore, in oxygen‐induced retinopathy (OIR) mice, the absence of Fpr2 was associated with diminished neovasculature formation and pathological vaso‐obliteration region in the retina. These results highlight the importance of Fpr2 in exacerbating the progression of neuroglial degeneration and angiogenesis in DR and its potential as a therapeutic target.